The Disintegration of Euro-Atlanticism and New Authoritarianism - Fouskas, Vassilis K. author. aut Link
XV, 211 p. 9 illus.
Keywords: “Fouskas and Gökay’s book about the Euro Crisis and German ambition is compelling. The context is the restructuring of the Euro-Atlantic assemblage by the global push of China. A must read.” –Werner Bonefeld, University of York, UK “This is an original, theoretically sophisticated, historically sensitive, and empirically grounded analysis.” –Bob Jessop, University of Lancaster, UK “Fouskas and Gökay have produced an extraordinarily impressive, carefully researched analysis of the contemporary global crisis.” –Alan W. Cafruny, Hamilton College, USA “This highly informative and stimulating book explores the larger picture in which the worrying symptoms of our time are unfolding at high speed. It makes an important and salutary contribution to the indispensable rethinking of ailing socialist politics.” –Gilbert Achcar, SOAS University of London, UK This book sets out a concrete analytical and empirical framework to understand the Euro-zone crisis and the deep disintegrative tendencies of Euro-Atlantic neo-imperialism. It explores how the authoritarianism and austerity led from above in the transatlantic world cultivate right-wing populism and racist hysteria from below, especially in relation to the global power-shift to China and other emerging economies. The authors argue that ordoliberal/neo-liberal austerity cannot reverse the decline of western economies; if anything, it precipitates their downfall and the re-launching of globalization under Asian primacy. The book will appeal to students, scholars and policymakers across the fields of International Political Economy, European Politics and Critical Social and Political Theory. Vassilis K. Fouskas is Professor of International Relations and Director of the Centre for the Study of States, Markets and People (STAMP) at the University of East London, UK. He is the founding editor of the Journal of Balkan and Near Eastern Studies. Bülent Gökay is Professor of International Relations at Keele University, UK, and the founding editor of the Journal of Global Fault-lines. Since 2008, he has been developing a historical analysis of the global financial crisis and economic downturn using the geological metaphor of ‘global fault-lines’.